The Ophthalmology Mini-Elective Gives Vision to Preclinical Medical Students - Mortensen, Peter (MedEdPORTAL, 2020)
INTRODUCTION: Ophthalmology education during medical school is often very limited. To provide exposure to areas beyond its standard curriculum, the University of Pittsburgh School of Medicine offers mini-elective courses in various disciplines. We developed such a course to provide instruction in the basics of clinical ophthalmology to interested preclinical medical students. METHODS: First- and second-year medical students electively enrolled in our course (mean number of students per year = 12), which included four sessions combining didactics and hands-on learning. Additionally, each student individually spent time with an ophthalmologist in the operating room. Our course was held each year from 2015 to 2019. RESULTS: Participants completed pre- (n = 25) and postsurveys (n = 20), reflecting increased comfort with the ophthalmologic history and physical examination. In 2019, participants also completed pre- and posttests, demonstrating increased knowledge of ophthalmology. DISCUSSION: The Ophthalmology Mini-Elective is a unique educational tool that introduces the principles of ophthalmology to preclinical medical students, addressing an area of medicine that is generally minimally included in the required curriculum.